2018
DOI: 10.12928/telkomnika.v16i3.8400
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of RFID Implementation on Warehouse Management System

Abstract: Logistic sector actors need innovation to improve competitiveness in providing their b est services to consumers, one of them on Warehouse Management System (WMS) b ecause the system is used to control the movement of the supply chain. There is a prob lem in one of Indonesia logistics companies on the process of selecting goods, so the warehouseman still di fficulties in this process. Thus, RFID implementation on WMS b ecomes one of the solutions to handle the goods selection process. This research uses Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
0
20
0
2
Order By: Relevance
“…For more progressed inquire about on data innovation, we prompt the readers who are interested to conduct a survey on the information of [3] and [13]. [14] demonstrated that when RFID is well developed, tested and implemented in any company, the accuracy should be 100%.…”
Section: Radio Frequency Identificationmentioning
confidence: 99%
“…For more progressed inquire about on data innovation, we prompt the readers who are interested to conduct a survey on the information of [3] and [13]. [14] demonstrated that when RFID is well developed, tested and implemented in any company, the accuracy should be 100%.…”
Section: Radio Frequency Identificationmentioning
confidence: 99%
“…In the previous study, the FMADM method was used for use in the field of financial investment evaluation [2], and attribute decision-making methods to find the optimal parking space in the [3] parking lot, and also used for the interest of high school students [4]. RFID application on WMS to handle the goods selection process [5]. Also, using this method, in retrospect to track the accuracy of the tracking result [6].…”
Section: Related Workmentioning
confidence: 99%
“…Warehouse activities normally include receiving, storing, order picking and shipping (Staudt et al, 2015). Warehousing plays an important role in the supply chain and has a significant effect on customer service (Calzavara et al, 2017;Indrawati et al, 2018;Pane et al, 2018). Due to increasing competition in the global logistics market, the uncertainty of demand, the potential for human error in labour-intensive processes and the growing interest in Industry 4.0, warehousing companies require technologies to improve their operational performance, make their systems more reliable and efficient and simplify their processes (Atieh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%